Human rights : a primer - "Blau, Judith; Esparza, Louis Edgar" (New York, 2016)
In an era of globalization and greater connectivity, human rights have come to the fore. Human rights depend on treaties but also increasingly on local and national laws and grassroots activism. The authors provide a basic introduction to human rights, and they unveil long-standing yet intensifying obstacles to attaining them-most notably the opposing logic of capitalism and of solidarity and collective struggles. They suggest ways to overcome these contradictions and create greater participation by the U.S. in the international community.
Keywords: Human rights